Mental toughness: Sounds great, but how do I develop it? - Gucciardi, D. (Elite Training Seminar Series, 2016)
In contexts where high performance underpins innovation, competitive advantage and success, there are few constructs that resonate deeply with people as that of mental toughness. Mental toughness is conceptualized as a personal capacity that enables individuals to high levels of subjective (e.g., goal pro-gress) or objective performance (e.g., sales, race time, GPA), despite everyday challenges and stressors as well as significant adversities. In this sense, mental toughness is considered per-tinent for major assaults (e.g., ACL injury) as well as acute (e.g., equipment malfunction) or chronic (e.g., controlling coach) stressors that can impede human functioning. Unsur-prisingly, researchers have devoted considerable effort to-wards understanding how to develop mental toughness. In this presentation, the speaker will review the latest evidence to provide insights into the strategies by which sport organisa-tions can foster mental toughness among athletes.